Effects of Sago Starch Types on Crackers from Edible Larvae of Sago Palm Weevils - Tuhumury, Helen; Souripet, Agustina; Nendissa, Sandriana (Department of Technology of Agricultural product (THP) Jambi University, 2020)
Sago starch and palm weevil larvae can be utilized as ingredients in crackers making to replace tapioca and prawn or fish. This research aimed to study the physicochemical and sensory properties of crackers made from three different sago starch, i.e., Molat, Ihur, and Tuni mixed with sago palm weevil larvae and to determine the best sago starch in making palm weevil larvae crackers. Results showed that Molat sago starch was the best option in making palm weevil larvae crackers. It resulted in crackers with better physicochemical and sensory properties than other sago starch. This cracker had the moisture, ash, protein, fat, fiber, and carbohydrate contents of 9.74, 1.17, 6.94, 0.45, 1.22, and 80.50%, respectively. The hardness of the un-fried crackers (17.19 N) was higher than that of others, while the fried crackers were lower (5.00 N). The crackers from Molat sago starch were liked by panelists in their taste and perceived to have a standard aroma. Whereas panelists extremely desired color, crispiness, and overall likeness. Crackers developed from Molat sago starch, and palm weevil larvae can fulfill the demands of nutritional security.